KEDAULATAN RAKYAT DALAM PEMIKIRAN FILSAFAT POLITIK MONTESQUIEU - Darussalam, Fajrul Ilmy; Indra, Andi Batara (Jurnal Politik Profetik, 2021)
The research of “Kedaulatan Rakyat dalam Pemikiran Filsafat Politik Montesquieu” is based on modern social-political condition. State life has a very broad coverage, not only limited to the relationship between individuals but also the form of power and freedom in individuals and state institutions. The public sovereignty becomes an interesting aspect in statehood issues as the role of citizens is reviewed according to the form of government in that country. The purpose of this study is to add another point of view of people's sovereignty through the perspective of Montesquieu's political philosophy. This research is classified as a literature of factual historical about a figure, using Montesquieu’s books as a primary literature and others political philosophy books which also criticize about public sovereignty as a secondary literature. This research using method of hermeneutics philosophy with elements description, holistic, historical continuity, and comparation. The results achieved in this study are, first, in the political philosophy of Montesquieu it is understood that there is a form of power needed to monitor or limit other powers. Second, popular sovereignty is the highest form of power in the hands of the people in a country. Third, major concept of Montesquieu political philosophy claim that there is a divided concept between institutional power in a country according to the functions and to actualize form of public sovereignty inside of a country.